2017
DOI: 10.1212/wnl.0000000000004576
|View full text |Cite
|
Sign up to set email alerts
|

Disparate effects of training on brain activation in Parkinson disease

Abstract: Exercise modifies brain activation patterns in patients with PD in a mode-specific manner. Motor-cognitive training decreased the reliance on frontal regions, which apparently resulted in improved function, perhaps reflecting increased brain efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(110 citation statements)
references
References 35 publications
10
90
1
7
Order By: Relevance
“…Only participants with PD were included in the review, and reported designs were therefore reassessed without including healthy controls and subsequently revised accordingly. In the study conducted by Maidan et al, it was decided that the control group would be considered the intervention group in this review, as we were interested in the physical exercise as opposed to the virtual reality (VR) component [19]. (2) Outcome measures used; (3) information on exercise type and intensity according to duration (number of weeks), frequency (sessions per week), and length of exercise (minutes per session); (4) sample characteristics regarding size, age, and Hoehn and Yahr stage; and (5) values (p values, confidence intervals, and effect sizes) and/or descriptives on posttraining result regarding neuroplasticity as well as other outcomes.…”
Section: Critical Appraisal Methodmentioning
confidence: 99%
See 3 more Smart Citations
“…Only participants with PD were included in the review, and reported designs were therefore reassessed without including healthy controls and subsequently revised accordingly. In the study conducted by Maidan et al, it was decided that the control group would be considered the intervention group in this review, as we were interested in the physical exercise as opposed to the virtual reality (VR) component [19]. (2) Outcome measures used; (3) information on exercise type and intensity according to duration (number of weeks), frequency (sessions per week), and length of exercise (minutes per session); (4) sample characteristics regarding size, age, and Hoehn and Yahr stage; and (5) values (p values, confidence intervals, and effect sizes) and/or descriptives on posttraining result regarding neuroplasticity as well as other outcomes.…”
Section: Critical Appraisal Methodmentioning
confidence: 99%
“…Seven different methods were used to measure neuroplasticity, and these were further operationalized into three domains: neurochemical (level of brain-derived neurotrophic factor (BDNF) in blood or serum (three studies) [28,31,33] and BDNF-TrkB signaling (one study)) [27], brain function (functional MRI (fMRI) (four studies) [19,32,34,35], electroencephalogram (EEG) (one study) [29], positron emission tomography (PET) (two studies) [26,36], transcranial magnetic stimulation (TMS) (one study)) [25], and brain structure (magnetic resonance imaging (MRI) (one study)) [34]. Assessment details are summarized in Table 1.…”
Section: Outcome Measures Of Neuroplasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…An obvious follow-on question is whether imagination of future events can be trained and whether such training facilitates waiting longer. Research in elderly participants [63] and in the motor domain [64] suggests that such interventions can result at least in changed imagery and brain responses.…”
Section: Waiting Longermentioning
confidence: 99%